3D micro- and nano-machining of hydrogenated amorphous silicon films on SiO2/Si and glass substrates. (3rd June 2015) - Soleimani-Amiri, S; Zanganeh, S; Ramzani, R; Talei, R; Mohajerzadeh, S; Azimi, S; Sanaee, Z
Abstract: We report on the hydrogen-assisted deep reactive ion etching of hydrogenated amorphous silicon ( a -Si:H) films deposited using radio-frequency plasma enhanced chemical vapor deposition (RF-PECVD). High aspect-ratio vertical and 3D amorphous silicon features, with the desired control over the shaping of the sidewalls, in micro and nano scales, were fabricated in ordered arrays. The suitable adhesion of amorphous Si film to the underlayer allows one to apply deep micro- and nano-machining to these layers. By means of a second deposition of amorphous silicon on highly curved 3D structures and subsequent etching, the fabrication of amorphous silicon rings is feasible. In addition to photolithography, nanosphere colloidal lithography and electron beam lithography were exploited to realize ultra-small features of amorphous silicon. We have also investigated the optical properties of fabricated hexagonally patterned a -Si nanowire arrays on glass substrates and demonstrated their high potential as active layers for solar cells. This etching process presents an inexpensive method for the formation of highly featured arrays of vertical and 3D amorphous silicon rods on both glass and silicon substrates, suitable for large-area applications.